PLANNING OF THE DOCTOR OF SCIENCES TRAINING PROJECT BY MICROSOFT OFFICE PROJECT (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article deals with the preparation of the doctor of sciences as a scientific project. The main indicators of doctoral students’ activity in Ukraine for the last nine years are presented. A brief review of domestic literary sources devoted to separate aspects of scientific projects was conducted. The characteristic features of the project of preparation of the doctor of sciences (purpose, available hierarchical goals, coordinated implementation of related actions, time frame, availability of budget, uniqueness) are indicated. Included in certain types of projects according to different classification features (scale / size, duration / terms of implementation, industry affiliation, functional orientation, nature of the involved parties, degree of complexity, composition and structure of the involved organizations, requirements to project quality, degree of binding, degree of connection, number of participants). The characteristics of the project (goal, vision and strategy, commercial benefits, organizational changes, time and costs) are listed. The processes associated with the project, which implement various management functions (initiation, planning, execution, monitoring and management, completion), are specified. The project of preparation of the doctor of sciences with Microsoft Office Project is planned. The budget and time limits of the project are indicated. For each project task the following information is provided: the number of the line in the project, the number in the structural decomposition of the work, the name, the cost of its implementation, the duration, the dates of beginning and end, the numbers of strings of predecessor tasks, the names of resources assigned to it, indicating the units or costs. The versatility of the developed project is that it can be applied to the work of the doctoral department of any institution of higher education (scientific institution) of Ukraine for the management of the preparation of doctors of sciences with outgoing changes in the duration of tasks, dates of their beginning and ending and the costs of their implementation. The draft project of preparation of the doctor of sciences can also serve as the basis for other scientific projects.
Keywords: scientific project, preparation of the doctor of sciences, planning, resources, Microsoft Office Project.